Association of the atherogenic index of plasma and high-sensitivity C-reactive protein with incident cardiovascular disease: evidence from a national cohort of middle-aged and older Chinese adults - Lian, Ping-an; Xie, Fei; Zhang, Wei; Cheng, Shuai; Zhao, Yun-fei; Li, Lin; Liang, Shan-fu; Zhu, Zhan-zhan; Zhang, Jun-yue; Cui, Jiao-jiao; Du, Jie; Yin, Lei; et al. (Frontiers in Endocrinology, 2025)
BackgroundThe atherogenic index of plasma (AIP), an emerging biomarker of lipid dysregulation, and high-sensitivity C-reactive protein (hs-CRP), an established marker of inflammation, are both implicated in the development of cardiovascular disease (CVD). However, their joint impact on CVD risk and the underlying mediation mechanisms remain unclear.MethodsThis study used data from the China Health and Retirement Longitudinal Study (CHARLS), including 8,763 adults aged ≥45 years with up to 9 years of follow-up. Baseline AIP and hs-CRP levels were measured, and participants were divided into four groups based on the AIP median and hs-CRP threshold (1 mg/L). Multivariable Cox models assessed associations with CVD. Mediation analyses examined direct and indirect effects, including bidirectional mediation. Additive interaction was evaluated using the relative excess risk due to interaction (RERI), and predictive performance was assessed via Receiver Operating Characteristic Curve (ROC) curve analysis.ResultsA total of 1,693 participants developed CVD during the follow-up period. Higher levels of AIP and hs-CRP were independently associated with CVD. Joint analysis showed that, compared with individuals with AIP below the median and hs-CRP <1 mg/L, those with elevated levels of both AIP and hs-CRP had the highest risks of CVD (HR: 1.655; 95% CI: 1.455-1.883), heart disease (HR: 1.402; 95% CI: 1.207-1.628), and stroke (HR: 2.207; 95% CI: 1.771-2.749). These associations remained significant after adjustment for potential confounders, although the effect sizes were attenuated. Notably, the effect of hs-CRP on increased CVD risk was more pronounced among individuals with higher AIP levels. Mediation analysis revealed that hs-CRP mediated 6.6% of the association between AIP and CVD (P=0.042), while AIP mediated 20.3% of the association in the reverse pathway (P=0.008). The RERI between AIP and hs-CRP for CVD was 0.141 (95% CI: -0.102 to 0.384), suggesting a possible positive additive interaction. The ROC analysis indicated that the combined model had better predictive performance for CVD than either marker alone (AUC = 0.590), with the best performance observed in stroke prediction (AUC = 0.615). Subgroup analyses confirmed consistent associations across demographic and clinical subgroups, except in individuals with prediabetes or diabetes.ConclusionsElevated levels of AIP and hs-CRP were independently and jointly associated with an increased risk of cardiovascular disease, particularly stroke. The observed mutual mediation effects and potential additive interaction suggest that lipid metabolism and inflammation may be interconnected in the pathophysiological processes underlying cardiovascular risk. These findings highlight the potential value of incorporating both biomarkers into cardiovascular risk assessment models to enhance early identification and prevention strategies among middle-aged and older adults.